EuPRAXIA conceptual design report - Assmann, R. W.; Weikum, M. K.; Akhter, T.; Alesini, P. D.; Alexandrova, A. S.; Anania, M. P.; Andreev, N. E.; Andriyash, I.; Artioli, M.; Aschikhin, A.; Audet, T.; Bacci, A.; et al. (European Physical Journal - Special Topics, 2020)
This report presents the conceptual design of a new Euro- pean research infrastructure EuPRAXIA. The concept has been established over the last four years in a unique collaboration of 41 laboratories within a Horizon 2020 design study funded by the Euro- pean Union. EuPRAXIA is the first European project that develops a dedicated particle accelerator research infrastructure based on novel plasma acceleration concepts and laser technology. It focuses on the de- velopment of electron accelerators and underlying technologies, their user communities, and the exploitation of existing accelerator infras- tructures in Europe. EuPRAXIA has involved, amongst others, the international laser community and industry to build links and bridges with accelerator science – through realising synergies, identifying dis- ruptive ideas, innovating, and fostering knowledge exchange. The Eu- PRAXIA project aims at the construction of an innovative electron accelerator using laser- and electron-beam-driven plasma wakefield ac- celeration that offers a significant reduction in size and possible sav- ings in cost over current state-of-the-art radiofrequency-based accelera- tors. The foreseen electron energy range of one to five gigaelectronvolts (GeV) and its performance goals will enable versatile applications in various domains, e.g. as a compact free-electron laser (FEL), compact sources for medical imaging and positron generation, table-top test beams for particle detectors, as well as deeply penetrating X-ray and gamma-ray sources for material testing. EuPRAXIA is designed to be the required stepping stone to possible future plasma-based facilities, such as linear colliders at the high-energy physics (HEP) energy fron- tier. Consistent with a high-confidence approach, the project includes measures to retire risk by establishing scaled technology demonstra- tors. This report includes preliminary models for project implemen- tation, cost and schedule that would allow operation of the full Eu- PRAXIA facility within 8–10 years.